1997
DOI: 10.1128/aac.41.7.1601
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of katG gene mutations in strains of Mycobacterium tuberculosis complex from Africa

Abstract: A sample of 124 isoniazid (INH)-resistant and 88 susceptible strains of Mycobacterium tuberculosis complex from south, central, and west Africa was analyzed by direct sequence analysis and PCR-restriction fragment length polymorphism analysis of their catalase-peroxidase (katG) genes. Point mutations at codon 315 were found in the genomes of 64% of INH-resistant strains, but no complete deletions were identified. Mutations at codon 463 were independent of INH resistance and were linked to the geographic origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
51
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 16 publications
11
51
0
Order By: Relevance
“…On the one hand, the S315T mutation is found most often (59.2%), as has been previously reported by others [10,11,19]. On the other hand, other mutations in this codon are found with a low frequency in Philippines strains (3.7%).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…On the one hand, the S315T mutation is found most often (59.2%), as has been previously reported by others [10,11,19]. On the other hand, other mutations in this codon are found with a low frequency in Philippines strains (3.7%).…”
Section: Discussionsupporting
confidence: 57%
“…Association between mutations in the katG gene and clinical isoniazid-resistant isolates was found in the early 1990s, when the primary mycobacterial catalase-peroxidase gene (katG) was cloned and sequenced [9]. A large number of studies have confirmed this discovery and different mutations have been described [10,11].…”
Section: Introductionmentioning
confidence: 84%
“…A common katG315 missense mutation (AGC ACC or ACA) with amino acid change of serine to threonine (Ser315 Thr) was described in various geographic areas (Haas et al, 1997;Abate et al, 2001), and about 10 to 25% of other mutations were located in different katG loci (Musser et al, 1996). Our sequencing results showed the presence of Ser315Thr in 17 isolates and allowed us to detect a novel mutation (katG T326D) in 2 MDR investigated strains.…”
mentioning
confidence: 79%
“…Our sequencing results showed the presence of Ser315Thr in 17 isolates and allowed us to detect a novel mutation (katG T326D) in 2 MDR investigated strains. This area of katG gene was chosen for sequencing investigation because the most frequently INH-resistance mutations occurred between codon 249 to codon 350 (Haas et al, 1997;Lavender et al, 2005;Guo et al, 2006;Hazbóm et al, 2006). None of the isolates had an entire deletion of katG, evidence of its rare occurrence in clinical isolates.…”
mentioning
confidence: 99%
“…Although a point mutation (AGC to ACC) resulting in Ser315Thr substitution is most common [9][10][11], other mutations involving codon 315 in the katG gene also occur in isoniazid-resistant strains [6][7][8][12][13][14]. The occurrence of ACC and other mutations at codon 315 of the katG gene varies considerably around the world and a high prevalence of ACC mutation has been exploited for developing a rapid molecular screen for the detection of majority of isoniazid-resistant M. tuberculosis isolates from a given geographical location [9,10,12]. The prevalence of AGC to ACC mutation in isoniazid-resistant M. tuberculosis isolates was found to vary from a low of 35% in Beirut (Lebanon) to 65-70% in Kuwait and Dubai (United Arab Emirates, UAE) [15,16].…”
Section: Introductionmentioning
confidence: 98%